Development of an AI-driven decentralized control for fifth generation district heating and cooling networks - Donner, Johannes Aurelius Tamino; Schlüter, Alexander (SDEWES Conference 2025)
Keywords: 5GDHC; district heating; DHC; waste heat; AI-Driven

Techno-economic analysis of hydrogen and green fuels supply scenarios assessing three import routes: Canada, Chile, and Algeria to Germany - Seeger, Karl; Genovese, Matteo; Schlüter, Alexander; Kockel, Christina; Corigliano, Orlando; Díaz Canales, Edith Benjamina; Praktiknjo, Aaron; Fragiacomo, Petronilla (International Journal of Hydrogen Energy)

Comparison of the economic efficiency and sustainability of two debonding processes for structurally bonded sills - Jordan, Alex; Hermelingmeier, Lucas; Gilich, Julian; Meschut, Gerson; De Santis, Marco Sebastian; Schlüter, Alexander (Journal of Advanced Joining Processes)
In light of growing demands for resource efficiency and sustainability in vehicle engineering, the environmentally compatible separation of structural adhesive joints is gaining increasing relevance. This study presents a comparative analysis of two physically based debonding methods: the established hot-air process and a cryogenic cold process based on liquid nitrogen (LN2). The primary objective is to assess the ecological impact and process-related sustainability of both approaches. Experimental investigations were conducted on a component-representative triple-sheet structure that simulates common automotive flange joints. Thermal input was applied either by convective heating using a hot air gun or by direct cooling through a contact-based LN2 tool. The resulting temperature profiles were recorded using spatially distributed thermocouples. Subsequently, the outer panel was selectively debonded to replicate a repair scenario, and the mechanical integrity of the remaining adhesive joint was evaluated through Mode I testing of L-shaped specimens. Process data served as input for an Life Cycle Assessment (LCA) according to DIN EN ISO 14040. The cryogenic method achieved a 40% reduction in carbon footprint compared to the hot-air process (0.337 kg vs. 0.559 kg CO2-equivalents), primarily due to its shorter process time and more efficient heat transfer. While the hot-air method’s impact is mainly driven by electrical energy use, that of the cold method stems from cryogenic media consumption. Notwithstanding certain disadvantages in specific impact categories, the LN2-based process exhibits a superior overall ecological performance and signifies a promising solution for repair- and recycling-oriented adhesive separation in structural vehicle applications.
Keywords: Sustainable debonding; Structural adhesives; Sustainable joining technologies; Life Cycle Assessment (LCA); Automotive repair process; Economically efficient debonding

Implementing Strategic Environmental Assessment in the Global South, a Challenge: Nicaragua as a Case Study - Díaz Canales, Edith Benjamina; Avila Galarza, Alfredo; Schlüter, Sabine; Lacayo Escobar, Erick; Schlüter, Alexander (Journal of Sustainable Development Indicators)

Hydrogen economy development in the European Union - Genovese, Matteo; Piraino, Francesco; Corigliano, Orlando; Schlüter, Alexander; Scionti, Eugenio; Fragiacomo, Petronilla (Accelerating the Transition to a Hydrogen Economy)

Influence of pre-shearing on the rheological properties of filled rubber compounds - Kleinschmidt, Dennis; Brüning, Florian (KGK Kautschuk Gummi Kunststoffe)
Keywords: Rheologie; Viskosität; Wandgleiten

Vorhersagemodell zum ortsaufgelösten Energieeintrag in dichtkämmenden Gleichdrall-Doppelschneckenextrudern - Austermeier, Laura

Die verarbeitungsinduzierte Glasfaserschädigung von Bulk Molding Compounds - Scholle, Maximilian

Effect of Strain Rate on the Deformation Behavior and Energy Absorption Characteristics of LPBF-Processed Ti2448 Microarchitectured Lattice Structures - Ghosh, Koustav; Milaege, Dennis; Steinmeier, Paul; Schaper, Mirko; Hoyer, Kay-Peter; Pramanik, Sudipta (Journal of Materials Engineering and Performance)

Life cycle engineering of lightweight structures in vehicles for on-demand mobility services - Ostermann, Moritz; Dierkes, Eric; Marten, Thorsten; Tröster, Thomas (Cleaner Engineering and Technology)
To reduce transport-related environmental impacts, innovative mobility system approaches such as on-demand services are being developed. These can include operating vehicles that differ regarding their characteristics and application profile from privately owned cars in motorized individual transport. Studies on life cycle assessment and life cycle engineering of vehicle lightweight structures are mainly limited to these privately owned cars and the impact category of climate change. In this paper, a method for life cycle assessment-based engineering of lightweight structures in vehicles for various mobility system applications, including on-demand mobility services, is developed. The method enables the holistic life cycle assessment of lightweight structures in different mobility system applications considering parameter changes at the upstream products, component, subsystem, vehicle and mobility system levels, as well as the integration of results into engineering activities. A case study is used to show that the vehicle and mobility system application of lightweight structures can significantly influence their environmental impacts and the selection of ecologically preferable product designs. The application in vehicles for on-demand mobility services can lead to an increase in absolute use stage energy demand and environmental impacts compared to applications in privately owned vehicles for motorized individual transport. However, normalized to the transport performance provided, the lifecycle environmental impacts of structural components in vehicles for on-demand mobility services can be lower than in vehicles for motorized individual transport. The paper contributes methodically and with quantitative results to improved decision making in life cycle engineering activities for lightweight structures in mobility system applications.
Keywords: Life cycle assessment; Life cycle engineering; Lightweight design; On-demand mobility; Shared mobility; Mobility services

Energy- and material-efficient Ti-6Al-4V sheet part fabrication by the novel TISTRAQ-process, including resistance heating and tool-based quenching: Insights into test stand design and material potential - Pfeffer, Nina; Kaiser, Maximilian Alexander; Feix, Werner; Kälble, Nils; Merten, Mathias; Stark, Andreas; Haufe, Andre; Meyer, Thomas; Tröster, Thomas; Höppel, Heinz Werner (Materials Science and Engineering: A)

Assessing solids conveying in injection moulding machines using coupled numerical simulations based on the discrete element method (DEM) and multibody systems (MBS) - Landgräber, Jan; Schöppner, Volker; Brüning, Florian (International Polymer Processing)
Abstract Design of single screw machines for polymer processing often focuses on the melt dominated areas of the screw. However, solids conveying is a key aspect for processes with high screw speeds, grooved feed sections, small screw diameters and material with low bulk density. In injection moulding, throughput limitations are highly relevant in packaging applications as due to low cooling times, plasticizing affects the cycle time. In addition, insufficient solids conveying is a primary cause for air residues in the melt and final product. Therefore, well-designed feed sections are required, especially as direct processing of regrind in recycling applications becomes more relevant due to governmental restrictions. Existing models for injection moulding are based on analytical equations and do not allow to assess new feed sections and feed opening designs, adapted to high screw speeds or regrind. In this paper, numerical simulations based on the Discrete Element Method (DEM), previously used in the field of extrusion, are carried out. In order to replicate the cyclic, superimposed rotation and translation of the screw, a coupled approach of DEM and Multibody Systems Simulation (MBS) is pursued. To verify the accuracy of such coupled simulations, a special test setup is added to a conventional injection moulding machine. Pure solids conveying is investigated, as DEM does not accommodate for large plastic deformations or melting. Different screw and intake designs as well as smooth and grooved barrels are investigated. Selected resins, pellet shapes and regrind are processed, varying the processing parameters and comparing the results to the simulation. The coupled approach replicates reality well in terms of throughput, confirming that DEM can be utilised to further investigate process phenomena and develop calculation models for solids conveying in injection moulding.

Untersuchung von Kombinationen aus Duroplasten und Elastomeren für den einstufigen 2K-Spritzgießprozess - Löhr, Florian; Moritzer, Elmar; Klie, Benjamin; Giese, Ulrich (Technomer 2025 - 29. Fachtagung über Verarbeitung und Anwendung von Polymeren)
Keywords: BMC; Duroplast; Kautschuk; Mehrkomponenten; Spritzgießen

Direkthaftung statt Klebstoff –Verbund von Duroplasten und Kautschuk im 2K-Spritzgießprozess - Löhr, Florian (AZuR-Kolloquium 2025)

Thermoset–Rubber 2K Composite Systems: Material Combinations and Interfacial Reactions in a One-Step Injection Molding Process - Löhr, Florian; Moritzer, Elmar; Klie, Benjamin; Giese, Ulrich (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: BMC; Duroplast; Kautschuk; Mehrkomponenten; Spritzgießen

Improvement of a numerical two-phase simulation model for single-screw plasticizing extruders based on experimental investigations - Knaup, Felix; Schöppner, Volker (International Polymer Processing)
Keywords: CFD simulation; melting modeling; melting process; polymer extrusion; single-screw extruder

Improving an Analytical Model of Melting in Single Screw Extruders considering the Delay Zone Length - Knaup, Felix; Brüning, Florian; Schöppner, Volker (Annual Technical Conference of the Society of Plastics Engineers (ANTEC 2025))
Keywords: Aufschmelzen; Aufschmelzmodellierung; delay zone; extrusion; melting modeling

Bestimmung der Feststoffbettfestigkeit zur Vorhersage von Feststoffbettbrüchen im Einschneckenextruder - Knaup, Felix; Brüning, Florian; Schöppner, Volker (Technomer 2025 29. Fachtagung)
Keywords: Aufschmelzen; Aufschmelzmodellierung; Feststoffbett; melting modeling

Characterization of the wall slip behavior of filled rubber compounds considering the critical wall shear stress - Kleinschmidt, Dennis; Schöppner, Volker (RubberCon 2025)
Keywords: Kautschuk; Rheologie; Wandgleiten

Findings on pinless screw design for rubber extrusion - Schmidt, Leon; Schöppner, Volker; Brüning, Florian (RubberCon 2025)
Keywords: extrusion; Kautschuk; Simulation